Efektivitas Infusum Daun Durian (Durio zibethinus) Sebagai Anestesi Alami Ikan Lele (Clarias gariepinus) - Taufik Budhi Pramono; Candro Bagaskara Yudhistira; Purnama Sukardi (Jurnal Sumberdaya Akuatik Indopasifik, 2020)
Artificial or natural anesthetic ingredients are needed in the transportation of live fish, because fish must be physiologically alive and healthy to their destination. Durian leaf is one of the natural ingredients that can be used as anesthetics in transport because it contains secondary metabolites such as saponins, tannins and flavonoids. The purpose of this study was to determine the effective concentration of durian leaf infusion as catfish anesthesia during transportation on induction and sedative time, blood glucose profile and survival rate. Fish with an average weight of 185,62 ± 9,06 g in 3 L of water with different concentrations of durian leaf anesthetics are used to determine the status of fish fainting. A complete randomized design (CRD) with four treatments (5%, 15%, 25%, and 35% durian leaf infusion concentrations) and three replications were applied in this study. The results of this study indicated that the best concentration obtained was 35%, with an inductive time of 9 min.19 sec. and a sedative time of 1 min.42 sec. The survival rate of catfish in the best treatment was 88.89%, with a blood glucose level of 63.23 mg/dL.